Investigating Lexical Diversity of Children Narratives: A Case Study of L1 Speaking - Rahayu, Famala Eka Sanhadi; Utomo, Aries; Setyowati, Ririn (UIN Salatiga, 2020)
Lexical diversity is one of the language tools to measure varied words or vocabulary produced by learners in a text both spoken and written. This research aims to investigate the lexical diversity of children narratives produced by children orally. The research design of this research was a case study supported by quantitative data. Meanwhile, the subjects of this research are seven children around 6-9 years old. In collecting data, the researchers employed narrative storytelling based on a picture which is drawn by the subjects. In analyzing data, TTR (Type-Token -Ratio) was used to measure the lexical diversity gained from the subject while the theory was used to explain the phenomena. Based on the findings, it is found that (1) older children have higher lexical diversity than the younger ones, (2) younger children produced higher lexical frequency (word tokens) than the older ones (3) individual variations caused an anomaly of the result in which older children were expected to have higher lexical frequency but the result showed the reverse. Keywords: Lexical Diversity, Children, Oral Narratives, Case Study.